Analisis Motiviasi Berprestasi Siswa serta Implikasinya dalam Pelayanan Bimbingan dan Konseling - Riska Andriani (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2019)
This research is motivated by the low achievement motivation of students. This study aims to describe the student achievement motivation. The research method used is descriptive quantitative.  population in this study is numbered 105 people. The sample consisted of 105 students, the sampling technique used saturated samples. The research findings show that students' achievement motivation is in the high category.